Pengembangan E-Modul Pembelajaran Instalasi Motor Listrik dengan Metode Example Non Example - Rama Miftahul Fauzi; Usmeldi Usmeldi (Jurnal Pendidikan Teknik Elektro, 2020)
The research and development aim to produce e-modules for learning electric motor installations. This research was motivated because the material in the e-modules used by the teacher did not cover all the basic competencies in the syllabus. This study uses a research and development method with a 4D model. The subject of this research is the e-module for learning electric motor installations using the Example Non Example method. Research respondents were students of class XI TITL 1 and teachers of the subject of Electrical Motor Installation. The research instruments were validation questionnaires, practicality questionnaires, and posttest questions. Data was collected using questionnaires and online posttest questions via google forms due to the Covid-19 outbreak. Data analysis used percentage and category techniques. The result of this research is the validity of e-module learning is in the valid category. The practicality of e-module learning falls into the practical category. The effectiveness of e-modules is categorized as effective. Thus e-learning modules can be used in learning.